A Screen for Candidate Targets of Lysine Polyphosphorylation Uncovers a Conserved Network Implicated in Ribosome Biogenesis - Amanda Bentley-DeSousa; Charlotte Holinier; Houman Moteshareie; Yi-Chieh Tseng; Sam Kajjo; Christine Nwosu; Giuseppe Federico Amodeo; Emma Bondy-Chorney; Yuka Sai; Adam Rudner; Ashkan Golshani; Norman E. Davey; et al. (Cell Reports, 2018)
Summary: Polyphosphates (polyP) are chains of inorganic phosphates found in all cells. Previous work has implicated these chains in diverse functions, but the mechanism of action is unclear. A recent study reports that polyP can be non-enzymatically and covalently attached to lysine residues on yeast proteins Nsr1 and Top1. One question emerging from this work is whether so-called “polyphosphorylation” is unique to these proteins or instead functions as a global regulator akin to other lysine post-translational modifications. Here, we present the results of a screen for polyphosphorylated proteins in yeast. We uncovered 15 targets including a conserved network of proteins functioning in ribosome biogenesis. Multiple genes contribute to polyphosphorylation of targets by regulating polyP synthesis, and disruption of this synthesis results in translation defects as measured by polysome profiling. Finally, we identify 6 human proteins that can be modified by polyP, highlighting the therapeutic potential of manipulating polyphosphorylation in vivo. : Bentley-DeSousa et al. screen yeast for proteins that undergo covalent modification by polyphosphate. They describe 15 substrates enriched for functions related to ribosome biogenesis. Homologs of these and other human proteins containing certain motifs can be “polyphosphorylated” using an ectopic expression system, providing a method to explore polyphosphorylation beyond yeast. Keywords: Vtc4, polyphosphate, lysine polyphosphorylation, ribosome biogenesis, Ppn1, Ppn2, yeast